Tax knowledge diffusion via strategic alliances - Jens Müller; Arndt Weinrich (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
This study examines strategic alliances as channels for tax knowledge diffusion between firms. Although strategic alliances are primarily expected to foster their main business purposes, we focus on whether tax knowledge potentially diffuses as a second order effect of peer-to-peer cooperation. To tease out diffusion of tax knowledge, we investigate changes in the tax planning behavior of high-tax firms in strategic alliances with low-tax firms in comparison to high-tax firms in strategic alliances with other high-tax firms. Our results suggest an economically meaningful decrease of high-tax firms' cash effective tax rates when cooperating with low-tax firms. Additionally, we find that this adjustment occurs within two years of a strategic alliance's initiation. We apply textual analysis to control for the strategic alliances' main business purposes in our analyses. Because these activities do not appear to drive our findings, we argue to identify tax knowledge diffusion as a second order effect and conjecture that strategic alliances are not intended to be tax planning investments. Finally, we test whether partner characteristics intensify or mitigate the identified effects. Overall, our results provide robust evidence for tax knowledge diffusion via strategic alliances.
Keywords: C31; G34; H26; 330; Corporate Tax Planning/Avoidance; Knowledge Diffusion; Network; Strategic Alliance